Karyomapping identifies second polar body DNA persisting to the blastocyst stage: implications for embryo biopsy. Issue 6 (December 2015) - Ottolini, Christian S.; Rogers, Shaun; Sage, Karen; Summers, Michael C.; Capalbo, Antonio; Griffin, Darren K.; Sarasa, Jonas; Wells, Dagan; Handyside, Alan H.
Abstract: Blastocyst biopsy is now widely used for both preimplantation genetic screening (PGS) and preimplantation genetic diagnosis (PGD). Although this approach yields good results, variable embryo quality and rates of development remain a challenge. Here, a case is reported in which a blastocyst was biopsied for PGS by array comparative genomic hybridization on day 6 after insemination, having hatched completely. In addition to a small trophectoderm sample, excluded cell fragments from the subzonal space from this embryo were also sampled. Unexpectedly, the array comparative genomic hybridization results from the fragments and trophectoderm sample were non-concordant: 47, XX, +19 and 46, XY, respectively. DNA fingerprinting by short tandem repeat and amelogenin analysis confirmed the sex chromosome difference but seemed to show that the two samples were related but non-identical. Genome-wide single nucleotide polymorphism genotyping and karyomapping identified that the origin of the DNA amplified from the fragments was that of the second polar body corresponding to the oocyte from which the biopsied embryo developed. The fact that polar body DNA can persist to the blastocyst stage provides evidence that excluded cell fragments should not be used for diagnostic purposes and should be avoided when performing embryo biopsies as there is a risk of diagnostic errors.